Whole body vibration increases hip bone mineral density in road cyclists - Prioreschi, A.; Oosthuyse, T.; Avidon, I.; McVeigh, Joanne (2012)
This study aimed to determine the effects of 10 weeks of whole body vibration training on the bone density of well-trained road cyclists. 15 road cyclists were assigned to either a vibrating group (n=8), who undertook 15 min of intermittent whole body vibration at 30 Hz, 3 times per week while continuing with their normal cycling training; or a control group (n=7), who continued with their normal cycling training for the 10-week period. Cyclists were age, body mass and height matched with 15 sedentary participants. At baseline, all participants underwent regional dual x-ray absorptiometry scans, where both cycling groups had lower pelvic (p<0.050) and higher head bone mineral density (p<0.050) than the sedentary participants with no other differences observed. After 10 weeks of training, vibrating cyclists showed a significantly greater increase in hip bone mineral density (0.020±0.010 g.cm 2 (1.65%), p=0.024) while the control cyclists ( 0.004±0.001 g.cm 2 (0%)) showed no change (p>0.050). The control group had a significantly lower spine bone mineral density (1.027±0.140 g.cm 2, p=0.020) compared to baseline (1.039±0.140 g.cm 2). This loss was not observed in the vibrating group. 10 weeks of whole body vibration training increased hip and preserved spine bone mineral density in road cyclists.